AN OVERVIEW OF CHILD ABUSE BY PARENTS IN ONLINE LEARNING DURING THE PANDEMIC COVID-19 ERA AND IT’S IMPACT IN REALIZING THE SDGs 2030 IN INDONESIA - Ahmad Rizky Farhan; Cindini Febriani; Dina Rafa Zahra (Khazanah: Jurnal Mahasiswa, 2021)
Background: Marriage is a new chapter in life with the aim of forming a happy and eternal family. However, during the Covid-19 pandemic, realizing this goal is increasingly difficult. This is related to problems that occur in the domestic sphere, such as a declining family economy and fights that trigger violence and even divorce. Basically, the problems that occur are also motivated by the form of the traditional family role division format in which the husband as the head of the family plays a public role to provide for his family and the wife only plays a domestic role as a housewife. Meanwhile, one of the goals of the Sustainable Development Goals is gender equality as in the target (5.1) to end all forms of discrimination against all women and girls everywhere, and (5.5) ensure women’s full and effective participation and equal opportunities for leadership at all levels of decision-making. Method: This study uses a systematic literature review method by collecting various relevant previous studies to be identified, reviewed, evaluated, and interpreted. Result: The results of this study indicate that in Indonesia there are still many socio-cultural influences on gender roles where men (husbands) do masculine tasks and women (wives) do feminine tasks. Therefore, there are still families who apply the traditional form of family role division. However, there are also families who have implemented equal roles in their families that are not fixed by gender. Conclusion: Therefore, it is necessary to apply a pattern of partnership relationships in the family and the role of the government to realize the target (5.4) to recognize and value unpaid care and domestic work through the provision of public services, infrastructure and social protection policies and the promotion of shared responsibility within the household and the family as nationally appropriate. Keywords: Domestic Works; Spouse; Gender Equality; SDGs 2030; Indonesia